Perhitungan Jumlah Kendaraan Bermotor Dengan Metode Manual Traffic Counting Di Wilayah Pengembangan II (WP II) Dan Wilayah Pengembangan III (WP III) Kota Pekanbaru - Gitamy Anggraini; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Transportation problems are a problem that is often faced by developed countries and developing countries such as Indonesia, both in the fields of urban transportation and inter-city transportation. The high growth rate of motorized vehicles, on the one hand, can encourage economic growth, but on the other hand it can cause environmental impacts including congestion and noise. The increase in the flow of vehicles in the city of Pekanbaru is not only seen in the middle of the city but can be seen in the Districts of Rumbai and Rumbai Pesisir which are development areas (WP) II and WP III caused by densities of settlements in the two regions as well as several private universities such as the Caltex Riau Polytechnic (PCR), Lancang Kuning University (UNILAK), recreational areas, markets and other shopping centers. The method used manual traffic counting is to use a manual counter tool and survey form sheets to calculate the number of vehicles passing directly at the research location. The results showed that the highest number of vehicles on the three roads that became the vehicle research sample in WP II and WP III based on peak times namely on Yossudarso Road occurred on Monday afternoon at 40,105 SMP / day, School Roads occurred on Saturday Afternoon at 36,363 SMP / day, and on Jalan Tegalsari the highest number of vehicles occurs on Monday Morning at 5,161 SMP / day. Keywords: Transportation, Vehicle, Manual Traffic Counting, WP II and WP III, Pekanbaru City